2017
DOI: 10.1016/j.ajhg.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ARMC9, which Encodes a Basal Body Protein, Cause Joubert Syndrome in Humans and Ciliopathy Phenotypes in Zebrafish

Abstract: Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by hypotonia, ataxia, abnormal eye movements, and variable cognitive impairment. It is defined by a distinctive brain malformation known as the "molar tooth sign" on axial MRI. Subsets of affected individuals have malformations such as coloboma, polydactyly, and encephalocele, as well as progressive retinal dystrophy, fibrocystic kidney disease, and liver fibrosis. More than 35 genes have been associated with JS, but in a subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 101 publications
1
72
0
1
Order By: Relevance
“…Single larvae were lysed for genotyping which revealed a very high mutation efficiency (94% of sequenced clones from 7 larvae had small insertions-deletions, the majority of which were frameshift mutations). Among the mutant F0 fish, a striking scoliosis phenotype was observed in juveniles (Supplemental Figure 5E), reminiscent of other ciliopathy mutants including armc9 CRISPR-F0 fish (24). Taken together, these results confirm that loss of togaram1 causes ciliopathy phenotypes in zebrafish and supports a role for togaram1 in ciliary function.…”
Section: Togaram1 Mutations Cause Ciliopathy Phenotypes In Zebrafishsupporting
confidence: 69%
See 3 more Smart Citations
“…Single larvae were lysed for genotyping which revealed a very high mutation efficiency (94% of sequenced clones from 7 larvae had small insertions-deletions, the majority of which were frameshift mutations). Among the mutant F0 fish, a striking scoliosis phenotype was observed in juveniles (Supplemental Figure 5E), reminiscent of other ciliopathy mutants including armc9 CRISPR-F0 fish (24). Taken together, these results confirm that loss of togaram1 causes ciliopathy phenotypes in zebrafish and supports a role for togaram1 in ciliary function.…”
Section: Togaram1 Mutations Cause Ciliopathy Phenotypes In Zebrafishsupporting
confidence: 69%
“…In this study, we identified a new JBTS-associated protein module that can be distinguished physically and functionally from the previously proposed JBTS protein network at the transition zone of primary cilia (41). Several components of this new module localize at the ciliary basal body (24) and at the proximal end of the ciliary axoneme (25,42). Mutations in the genes encoding two directly interacting members of the module, ARMC9 and TOGARAM1, result in defects in cilium length, microtubule post-translational modifications (acetylation and polyglutamylation), and ciliary stability in patient-derived fibroblasts, zebrafish mutants, and genetically edited hTERT-RPE1 cell lines (Summary Figure 9).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…According to a recent study, about 55%~60% patients with Joubert syndrome are caused by the known gene mutations [62]. To date, there are about 30 genes to be associated with Joubert syndrome or Joubert syndrome related disorders (NPHP1, AHI1, ARMC9, CEP290, RPGRIP1L, TMEM67, CC2D2A, ARL13B, INPP5E, OFD1, TMEM216, CEP41, TMEM237, TCTN2, KIAA0556, KIF7, TCTN1, TMEM138, MKS1, C5ORF42, TMEM231, TCTN3, CSPP1, PDE6D, IFT172, ZNF423, TTC21B, B9D1, B9D2, and C2CD3) by target sequencing [63][64][65], indicating genetic heterogeneity of Joubert syndrome to a large extent.…”
Section: Joubert Syndromementioning
confidence: 99%